Patient-Reported Outcomes in Orthopaedics. (7th March 2018) - Christensen, Daniel L.; Dickens, Jonathan F.; Freedman, Brett; Mauntel, Timothy; Owens, Brett D.; Potter, Benjamin K.; Provencher, Matthew; Tokish, John M.; Waterman, Brian R.; Antosh, Ivan; Bellamy, Jaime; Cameron, Kenneth L.; et al.
Abstract : Patient-reported outcomes (PROs) assess a patient's perspective of health, function, and quality of life associated with health conditions and medical interventions. Health-care value is the ratio of health outcomes achieved relative to the total cost of care for a medical condition. Common PRO designs assess general quality of life, system or region-specific conditions, disease-specific conditions, or mixed outcome measure designs. Patient-Reported Outcomes Measurement Information System (PROMIS) measures domains of health (e.g., fatigue, physical function, and depressive symptoms), not disease or injury-specific outcomes, allowing for comparability across conditions and normative scoring. PROs offer a unique format to the clinician for understanding the impact of medical conditions or interventions and, as a result, may improve the care provided.